2002
DOI: 10.1152/japplphysiol.00150.2002
|View full text |Cite
|
Sign up to set email alerts
|

Decreased airway narrowing and smooth muscle contraction in hyperresponsive pigs

Abstract: Increased smooth muscle contractility or reduced smooth muscle mechanical loads could account for the excessive airway narrowing and hyperresponsiveness seen in asthma. These mechanisms were investigated by using an allergen-induced porcine model of airway hyperresponsiveness. Airway narrowing to electric field stimulation was measured in isolated bronchial segments, over a range of transmural pressures (0-20 cmH 2O). Contractile responses to ACh were measured in bronchial segments and in isolated tracheal smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In distinction to these findings, Ma and co-workers [114] have shown increased absolute shortening potential and velocity of shortening, as well as increased MLCK (myosin light chain kinase) gene expression, in asthmatic cells isolated from biopsies. Ex vivo studies of airway segments from hyperresponsive animals with structural changes induced by chronic allergen challenge have, paradoxically, sometimes shown decreased contractility or maximal shortening compared with controls [115,116]. Consistent with this, in an explant model in which smooth muscle hypertrophy and increased matrix was induced by cytokines, we showed decreased contractile responsiveness [80].…”
Section: Relationship Between Responsiveness and Remodellingsupporting
confidence: 84%
“…In distinction to these findings, Ma and co-workers [114] have shown increased absolute shortening potential and velocity of shortening, as well as increased MLCK (myosin light chain kinase) gene expression, in asthmatic cells isolated from biopsies. Ex vivo studies of airway segments from hyperresponsive animals with structural changes induced by chronic allergen challenge have, paradoxically, sometimes shown decreased contractility or maximal shortening compared with controls [115,116]. Consistent with this, in an explant model in which smooth muscle hypertrophy and increased matrix was induced by cytokines, we showed decreased contractile responsiveness [80].…”
Section: Relationship Between Responsiveness and Remodellingsupporting
confidence: 84%
“…The similar diameters of airways in vivo and in vitro confirm a common anatomical location. Secondly, unlike previous studies [2,33], excised airway segments were exposed to a similar volume history seen in vivo by oscillating Ptm at amplitudes and frequencies mimicking ventilation. The authors recently demonstrated that bronchoconstrictor responses to EFS in porcine bronchial segments are enhanced after periods of pressure oscillation [34], emphasising the importance for recording airway narrowing under similar conditions in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, swine models have emerged as excellent tools to study human pulmonary diseases, including cystic fibrosis [11], respiratory distresses in neonates [12], and asthma [13,14]. The availability of the pig genome sequence [15,16] together with metagenomic datasets of organic dust microbiomes[17**,18**] provide insight for investigating and understanding mechanisms of clinical manifestations of farm exposures.…”
Section: Introductionmentioning
confidence: 99%